The Effect Of Productive Zakat Fund Distribution On Improving Community Welfare Through Laz Dompet Dhuafa In Serang City - Sholahuddin; M. Sulaeman Jajuli (LP2M IAIN Palopo, 2026)
This study aims to analyze the influence of the distribution of productive zakat funds on improving community welfare through the Dompet Dhuafa Zakat Institution (LAZ) in Serang City. Zakat is not only understood as an individual religious obligation, but also as a socio-economic instrument that plays a role in equalizing welfare and alleviating poverty. The study uses a descriptive method with a qualitative approach through observation, interviews, and documentation techniques, and is analyzed using the stages of data reduction, data presentation, and conclusion verification. The results show that the distribution of productive zakat in the form of business capital, mentoring, and training can increase the economic capacity of mustahik, strengthen production assets, and foster the independence of micro-enterprises. In addition to its economic impact, productive zakat also fosters business ethics, financial discipline, and social solidarity among beneficiaries. Although limited funds cause assistance to be partial, the integration of non-zakat funding sources such as infaq and sadaqah is an effective strategy in expanding the program's reach. With planned and data-driven institutional management, productive zakat has been proven to contribute to the socio-economic transformation of mustahik from recipients to potential zakat givers, thus functioning as a holistic and sustainable development instrument.